Influence of Working Hours, Education and Amount of Dependence Family to Income of Women Lontar Craftsman in Bona Village, Gianyar - Ni Kadek Dwi Yuli Yastini Dewi; Made Henny Urmila Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Bona Village is one of the villages in Gianyar Regency where the majority of women work in the informal sector, namely as palm palm craftsmen. The aim of this research is to analyze the influence of working hours, recent education, and number of family dependents on the income of women palm palm craftsmen in Bona Gianyar Village. The number of samples used was 90 people using probability sampling techniques , namely simple random sampling. The research instrument uses a questionnaire in the form of several questions which will be distributed directly to the research location. The collected data was then tested and analyzed using multiple linear regression analysis with the SPSS 26 program. The research results showed that. 1) Working hours, education level, and number of family dependents have a simultaneous influence on the income of women palm leaf craftsmen in Bona Village, Gianyar. 2) Working hours, education level, and the number of family dependents has a partial positive effect on the income of women palm leaf craftsmen in Bona Village, Gianyar. The implications of this research consist of theoretical and practical implications. Theoretically, this research supports the concept of human capital theory in the form of investment in education, time allocation theory in working hours and income theory in the production results produced.